2020
DOI: 10.1155/2020/9421964
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and Practice on Hepatitis B Infection Prevention and Associated Factors among Health Science Students in Woldia University, Northeast Ethiopia

Abstract: Background. Hepatitis B virus is a global problem, with 66% of all the world population living in areas where there are high levels of infection. HBV is the leading risk factor for HCC globally and accounts for at least 50% of cases of HCC. Medical and health science students, being part of the health-care system, are exposed to the infection as a risk as other health-care workers when they come in contact with patients and contaminated instruments. Objective. The main aim of this study was to assess the knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 13 publications
(16 reference statements)
8
25
7
Order By: Relevance
“…Moreover, a study conducted in Pakistan reported that the knowledge level among medical students was 57.1% [15]. Our nding is slightly higher than that of a study conducted among health science students in Woldia University, Northeast Ethiopia; (52%) showed good knowledge about HBV [16]. In addition, our nding is greater than that reported by a study conducted in Saudi Arabia, in which 50% of medical students at the University of Dammam had good knowledge about HBV [17], also a study conducted among preclinical medical students of a medical college in Nepal reported that 50.8% had good knowledge regarding hepatitis B [18].…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…Moreover, a study conducted in Pakistan reported that the knowledge level among medical students was 57.1% [15]. Our nding is slightly higher than that of a study conducted among health science students in Woldia University, Northeast Ethiopia; (52%) showed good knowledge about HBV [16]. In addition, our nding is greater than that reported by a study conducted in Saudi Arabia, in which 50% of medical students at the University of Dammam had good knowledge about HBV [17], also a study conducted among preclinical medical students of a medical college in Nepal reported that 50.8% had good knowledge regarding hepatitis B [18].…”
Section: Resultscontrasting
confidence: 67%
“…In parts II, III, and IV of the questionnaire, participants' responses were compared with a standard template, and one mark was assigned for each correct response. The knowledge score was calculated by summing the marks of questions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Good knowledge was de ned by answering ≥ 70% of the knowledge questions correctly, whereas poor knowledge was de ned as < 70% of correct answers.…”
Section: Methodsmentioning
confidence: 99%
“…This is different to some other studies that showed the most common reasons for non-compliance is lack of resources. [ 8 9 ] This suggests that student factors might affect the vaccination compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Resource limitation was the most common reason for non-vaccination. [ 9 ] Another study conducted in a tertiary care teaching hospital in Telangana, South India, revealed 84% of the 94 medical students knew about HBV infection but only 24% were vaccinated. [ 10 ] While Locally, one cross-sectional study done at Unaizah College of Medicine, Qassim, found that only 21% of 321 students had good knowledge about HBV infection and prevention and only 41.4% of the students were vaccinated against HBV.…”
Section: Introductionmentioning
confidence: 99%
“…A cross sectional study on knowledge, attitude, and practice towards hepatitis B virus among pregnant women attending antenatal care at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia was done by Gebrecherkos et al [22]. The study showed that lack of Knowledge may influence the attitudes of the mother towards interventions that could reduce the risk of transmission to their infants.…”
Section: Attitude and Practices Towards Hepatitis B Infectionmentioning
confidence: 99%